Patients' experiences and preferences for primary care delivery: a focus group analysis. (24th June 2019) - Norwood, Patrícia; Correia, Isabel; Veiga, Paula; Watson, Verity
Abstract: Background: In 2005, the Portuguese government launched a primary care (PC) reform. After a promising start, the reform is still incomplete and has been compromised by low investment. The incomplete nature of the reforms has resulted in the coexistence of different models of care delivery and heterogeneity in resource allocation and performance. PC has been extensively evaluated, but little is known about the patients' views and preferences regarding PC and the ongoing reform. Aim: This study aims to examine patients' experiences of and preferences for PC in Portugal and to explore their experience of the recent reforms. Methods: A qualitative study was undertaken which collected data from eight focus groups in the city of Braga, Portugal. Participants were recruited with the collaboration of eight local institutions. Focus groups' discussions focused on patients' experiences of and preferences for PC as well as their views on the reforms. Audio recordings were transcribed and analysed using an inductive thematic content analysis. Findings: The majority of participants perceived that the reform was positive. However, the improvements achieved by the reform were insufficient to lead to most participants having a positive experience of PC delivery in Portugal. Participants' satisfaction/dissatisfaction with primary care was strongly associated with interpersonal relations and communication with doctors. Participants valued continuity of care, but felt the levels of responsiveness, flexibility and coordination in the current system were still unsatisfactory. Access and waiting times were seen as challenging and led participants to seek PC from emergency departments and private doctors. Policy Implications: The perception of increased inequity and the lack of effective choice undermined the social acceptability of the reform. Policies aimed at improving doctor–patient communication and continuity of care, as well as choice, may therefore lead to better satisfaction and more efficient use of health care settings.